Criminal Liability of Correctional Officers for Crimes Based on the Code of Ethics of the Minister of Law and Human Rights Regulation M.HH-16.KP.05.02/2011 - Kurniati, Yeti; Permana, Yedi Widya; Hassanah, Nurul; Awaludin, Agus; Randiana, Prasetia; Lambouw, Giovani Anggasta Pratiwi; Rahim, Abdul (Civiliza Publishing, Indonesia., 2025)
Correctional officers hold a vital position within Indonesia’s criminal justice system, responsible for ensuring rehabilitation, supervision, and the protection of inmates’ rights. However, numerous cases of misconduct ranging from drug trafficking, corruption, to human rights violations have raised serious concerns about accountability and the effectiveness of ethical governance. This study aims to analyze the criminal liability of correctional officers involved in crimes, viewed through the framework of the Minister of Law and Human Rights Regulation No. M.HH-16.KP.05.02/2011 concerning the Code of Ethics for Correctional Officers. Using a normative juridical method with statutory and conceptual approaches, data were collected from legislation, legal literature, and relevant case studies. The findings reveal that the regulation only provides moral and administrative sanctions without direct criminal implications, meaning that criminal responsibility must rely on general and special criminal law provisions. The study concludes that a strong synergy between the ethical code and criminal law is urgently needed to create a more effective, fair, and accountable correctional system. This research contributes to strengthening the legal framework of correctional ethics and promoting institutional integrity within Indonesia’s justice sector.